(untitled) (Desarrollo, Estado y Espacio, 2024)
In this article, we analyze the production and the political dynamics between human and non-human population in Islas de Santa Fe National Park, Argentina (2010-2023). Our research focuses on the institutional frameworks within singular sociopolitical contexts, examining their changes and continuities over time, as well as the political dynamics that link humans and non-humans in the protected area, their meanings, the social practices that are promoted and the ones that are neglected. Through the conceptual framework of Latin-American political ecology (whose approach critically articulates the struggles between multiples forms of appropriation of nature with a focus on power asymmetries historically shaped), we approach conservation of nature as an ecological process but also as a political one that involves the governance of territories and human and non-human populations through technologies of power that shape territories and social dynamics. Through qualitative data analysis, we identified two distinct phases: the first period (2010-2019) was characterized by a strict conservation model with the exclusion of human populations (as well as non-human populations contrary to the modern imaginary of what nature is in the Parque Nacional Islas de Santa Fe should be), and the second period (2020-2023) was oriented towards the development of institutional actions to organize human coexistence and their relationships with the environment under new engagement logics.